Northeast Asia in focus: Life, work and industry between the Steppe and the Metropoles, 1900-2020. Essays in commemoration of Flemming Christiansen's retirement - Festschrift - Christine Moll-Murata (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2022)
Flemming Christiansen retired in March 2020 from the position of Professor of Social Sciences of East Asia and Political Sociology of China at the University of Duisburg-Essen in Germany. To mark the occasion, his friends and colleagues from the study group on Northeast Asia present him with a volume of collected essays on the topics they have worked on together in recent years.
Keywords: 330